Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Carbon dioxide capture by metal organic frameworks - Saha, Subhadeep; Chandra, Suman; Garai, Bikash; Banerjee, Rahul (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
The design and synthesis of functionalized metal organic framework materials (MOFs) for reversible physisorption of CO2 is discussed. This strategy of CO2 adsorption in MOFs requires less energy for regeneration than materials relying on chemisorption. As a result the MOFs have received considerable attention as sorbent materials for strategic gases such as CO2 and H,. In this review, we have discussed different MOFs and hybrid materials containing MOFs which can adsorb CO2 at room temperature. In order to achieve high adsorption capacity, fast CO2 adsorption-desorption and low energy requirement for regeneration are necessary. Several avenues for increasing the CO2 adsorption capacity of such materials, for instance, introduction of open metal sites and the use of ligand molecules with specific functionalities (like -OH or -NH2) have been described. It has been observed that CO2 loading capacity of MOFs increases with functionalization. Herein, we have discussed how N-containing and fluorinated MOFs are designed to achieve higher CO2 loading than their non-functionalized counterparts. Nanocarbons (e.g. carbon nanotubes, carbon nanofibres, etc.) are porous materials and a blend of these porous materials with porous MOFs or porous carbon derived from MOFs may act as a better adsorbate than even the pure materials. Enhancement of CO2 loading by nanocarbon-MOF hybrid material is also discussed.
Keywords: Carbon dioxide adsorbents; Carbon dioxide capture; hybrid materials; Metal organic frameworks; Nanocarbons; Porous nanocarbons

Competition between gelation and crystallisation of a peculiar multicomponent liquid system based on ammonium salts - Kapoor, Iti; Schoen, Eva-Maria; Bachl, Jurgen; Kuehbeck, Dennis; Cativiela, Carlos; Saha, Subhadeep; Banerjee, Rahul; Roelens, Stefano; Juan Marrero-Tellado, Jose; Diaz, David Diaz (Soft Matter, 2012)
An exemplar competition between gelation and crystallisation phenomena was examined with an unusual synergistic multicomponent (organo) gelator solution (MGS), which consists of a well-defined methanolic solution of (1R, 2R)-1,2-diaminocyclohexane L-tartrate containing 2.4 equiv. of concentrated hydrochloric acid. The optimal composition of the MGS was determined through meticulous solubility, gelation and structural studies, which support a transient gelation mechanism based on the kinetic self-assembly of the tartrate salt driven by hydrogen-bonding interactions, involving ammonium nitrogen donors and hydroxyl oxygen acceptors, and electrostatic interactions. The hydrochloric acid is involved in the solubilisation of the salt through an ionic dissociation-exchange process, which ends up with the formation-precipitation of (1R, 2R)-1,2-diaminocyclohexane dihydrochloride. As a consequence, an irreversible destruction of the gel takes place, which indicates the metastable nature of this phase that cannot be accessed from the thermodynamically equilibrated state. Gelation of a variety of oxygenated and nitrogenated solvents with moderate polarity occurred efficiently using extremely low MGS concentrations at low temperatures, and the gel phase was confirmed by dynamic rheological measurements. Several features make the described MGS unique: (1) it is a multicomponent solution where each component and its stoichiometry play a key role in the reproducible formation and stabilization of the gels; (2) it is formed by simple, small, and commercially available chiral building blocks (dissolved in a well-defined solvent system), which are easily amenable for further modifications; (3) the gelation phenomenon takes place efficiently at low temperature upon warming up the isotropic solution, conversely to the typical gel preparation protocol; and (4) the formed organogels are not thermoreversible despite the non-covalent interactions that characterize the 3D-network.

Proton-conducting supramolecular metallogels from the lowest molecular weight assembler ligand: a quote for simplicity - Saha, Subhadeep; Schoen, Eva-Maria; Cativiela, Carlos; Diaz, David Diaz; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Oxalic acid has been proven to be the lowest molecular weight organic ligand able to form robust supramolecular metallogel networks in the presence of metal salts. In particular, two novel multifunctional metallogels were readily prepared at room temperature by simple mixing of stock solutions of Cu-II acetate monohydrate or Cu-II perchlorate hexahydrate and oxalic acid dihydrate. Formation of different polymorphs and unprecedented proton conduction under anhydrous conditions were also demonstrated with some of these materials.
Keywords: Copper; low-molecular-weight ligands; metallogels; proton conductivity; supramolecular chemistry

Salt metathesis in three dimensional metal-organic frameworks (MOFs) with unprecedented hydrolytic regenerability - Kundu, Tanay; Sahoo, Subash Chandra; Saha, Subhadeep; Banerjee, Rahul (Chemical Communications, 2013)
{Eight Zn-based porous (1.2 nm) homochiral MOFs (ValZnX, AlaZnX

Amino acid-based multiresponsive low-molecular weight metallohydrogels with load-bearing and rapid self-healing abilities - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
A multiresponsive metallohydrogel based on an amino acid-derived low molecular weight (LMW) ligand and a Zn(II) salt was prepared. This hydrogel showed remarkable shape-persistent, self-standing, load-bearing and self-healing properties, which is uncommon in LMW hydrogels.

Dissolvable metallohydrogels for controlled release: evidence of a kinetic supramolecular gel phase intermediate - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
Two metallohydrogels based on an amino acid-based ligand and Zn(II) salts were synthesized. These hydrogels show an uncommon, reversible, time-dependent transformation from the opaque to transparent state. These hydrogels also exhibit gradual dissolution in water (pH <= 7) over time. A water-soluble stimulant, caffeine, could be in situ loaded into the hydrogels and slowly released during dissolution.

Distinctive PdCl2-mediated transformation of Fe-based metallogels into metal-organic frameworks - Aiyappa, Harshitha Barike; Saha, Subhadeep; Garai, Bikash; Thote, Jayshri; Kurungot, Sreekumar; Banerjee, Rahul (Crystal Growth & Design, 2014)
Simple, efficient conversion of viable Fe3+-based metallogels into Fe-metal-organic frameworks (MOFs) has been achieved by PdCl2-mediated gel degradation. The metallogels and the resulting MOFs have been characterized, and a probable mechanism for the event has been elucidated.

Photocatalytic metal-organic framework from cds quantum dot incubated luminescent metallohydrogel - Saha, Subhadeep; Das, Gobinda; Thote, Jayshri; Banerjee, Rahul (Journal of the American Chemical Society, 2014)
Cadmium sulfide (CdS) quantum dots (<10 nm in size) have been successfully synthesized in situ without any capping agent in a Zn(II)-based low-molecular-weight metallohydrogel (ZAVA). Pristine ZAVA hydrogel shows blue luminescence, but the emission can be tuned upon encapsulation of the CdS quantum dots. Time-dependent tunable emission (white to yellow to orange) of the CdS incubated gel (CdS@ZAVA gel) can be attributed to sluggish growth of the quantum dots inside the gel matrix. Once CdS quantum dots are entrapped, their augmentation can be stopped by converting the gel into xerogel, wherein the quantum dots remains embedded in the solid xerogel matrix. Similar size stabilization of CdS quantum dots can be achieved by means of a unique room-temperature conversion of the CdS incubated ZAVA gel to CdS incubated MOF (CdS@ZAVCl) crystals. This in turn arrests the tunability in emission owing to the restriction in the growth of CdS quantum dots inside xerogel and MOF. These CdS embedded MOFs have been utilized as a catalyst for water splitting under visible light.

Fe(III) phytate metallogel as a prototype anhydrous, intermediate temperature proton conductor - Aiyappa, Harshitha Barike; Saha, Subhadeep; Wadge, Pritish; Banerjee, Rahul; Kurungot, Sreekumar (Chemical Science, 2015)
A proton conducting metallogel [FNPA; ferric nitrate (FN)-phytic acid (PA)] is synthesized by immobilizing a protogenic ligand (phytic acid) using iron(III) nitrate in DMF. The xerogel shows high proton conductivity of 2.4 x 10(-2) S cm(-1) at 120 degrees C, the best value known among all metal organic materials (MOMs). Marking the first such attempt in MOMs, an electrode made using the xerogel showed a power density of 0.94 mW cm(-2) at 0.6 V under dry fuel cell conditions.

Supramolecular metallogel that imparts self-healing properties to other gel networks - Feldner, Tobias; Haering, Marleen; Saha, Subhadeep; Esquena, Jordi; Banerjee, Rahul; Diaz, David Diaz (Chemistry of Materials, 2016)
A unique proton conductive and moldable supramolecular metallogel (CuA-Ox-gel) made upon mixing at room temperature well-defined stock solutions of Cu(OAc)(2). H2O and oxalic acid dehydrate was found to have self-healing properties. Remarkably, the system also displayed an unprecedented ability to impart self-healing properties to other gel networks lacking this capacity. A self-healed CuA-Ox metallogel was found to have essentially the same nanofibrillar morphology, thermal stability, rheological properties, and conductivity as the freshly prepared sample. The discovery also allowed the fabrication of self-healing conductive composites containing conductive carbonaceous materials. Overall, this work serves as a proof of concept for the transfer of self-healing properties between completely different gel networks.

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.